Self-Injurious Behavior in Children With Developmental Disabilities: A Systematic Review of Behavioral Intervention Literature. Issue 4 (July 2018) - Erturk, Buket; Machalicek, Wendy; Drew, Christine
We reviewed single-case research studies examining the effects of behavioral interventions for self-injurious behavior (SIB) in young children with autism and developmental disabilities. Systematic searches of electronic databases, journals, and reference lists identified 46 studies (66 participants younger than the age of 12) meeting inclusion criteria. Studies were examined based on (a) participant demographics, (b) topography and function of SIB, (c) type of functional behavior assessment (FBA), (d) intervention procedures and outcomes, and (e) experimental design and measurement. Intervention strategies were categorized as antecedent manipulations, teaching behavior, consequence-based procedures, and/or extinction procedures. Positive outcomes were reported for 78% of participants in the reviewed studies and 88% of the participants were diagnosed with autism. Results suggest the effectiveness of behavioral interventions to decrease SIB for young children with disabilities; however, the frequent use of packaged interventions without component analysis limits the conclusiveness of any treatment recommendation. Suggestions for future research are discussed.